ANALYSIS OF CALCULATION, RECORDING AND WITHHOLDING OF ARTICLE 23 INCOME TAX ON FREIGHT FORWARDING SERVICES (CASE STUDY AT PT. FREIGHT CARGO LOGISTICS) - Endah Prawesti Ningrum; Gina Amartia (Universitas Pelita Harapan, 2022)
Income Tax (PPh) article 23 is a tax withheld on income received by domestic taxpayers as well as permanent forms of business originating from capital. One of the services contained in PPh article 23 is freight forwarding services. This study aims to determine the mechanism for calculating, recording, and withholding income tax article 23 on freight forwarding services at PT. Freight Cargo Logistics in 2020 to 2021 and the suitability of calculating, recording, and withholding income tax article 23 for freight forwarding services at PT. Freight Cargo Logistics with Minister of Finance Regulation 141/PMK.03/2015. The research method used in this research is descriptive qualitative. The primary data from this study were obtained directly from PT. Freight Cargo Logistics which consists of withholding evidence for 2020 and 2021, a list of withholding evidence of Article 23 Income Tax, Article 23 Income Tax Returns. Imposition of income tax rates withheld by PT. Freight Cargo Logistics to vendors with NPWP are subject to 2% of the basic withholding tax (tax object value). The results of this study indicate that the implementation of calculations, recording, and deductions from PT. Freight Cargo Logistics complies with the current tax regulations.